Análise de genótipos de soja quanto à resistência ao nematoide do cisto - Juliatti, Breno Cezar Marinho (2015)
The nematodes are very abundant, as they represent 80% of individuals in the kingdom Animalia. The soybean cyst nematode (SCN), Heterodera glycines, is a great problem for soybean cultivation and it is present in about ten states of Brazil. Some species or soybean cultivars have the characteristic of resistance or alteration in survival skills and perpetuation of nematodes (female index FI), which process is activated when the nematode parasitism process starts; so the development of new resistant cultivars is primordial to the preservation of plant productivity. The objective of this study was to identify the reaction of 101 genotypes of soybeans in the Germplasm Laboratory of Federal University of Uberlândia (LAGER/UFU) improvement program, with inoculation of 4,000 H. glycines race 3 eggs. The experiment was conducted in a greenhouse room of UFU, where seeds of the genotypes and two standards, one susceptible (M-SOY 8866) and the other resistant (BRSGO Raissa) were sown in plastic cups of 500mL containing solarized mixture of soil and sand (1: 2). The tests followed a randomized block design (RBD), with five replications. Evaluations were made 35 days after inoculation on the basis of fresh and dry weight of roots, root volume, number of females (NF) and females index (FI). Genotypes 46 (F5: 6 BRSGO Caiapônia X 100 IAC) and 11 (Engopa 316 RR - Sel 4) performed moderate resistance; the genotype 61 (F5: 6 Caiapônia X Potenza) had moderate susceptibility; and the rest of the genotypes presented as susceptible. In the genotypes, NF ranged from 9.5 to 159.7 and FI ranged from 17 to 214.8. The coefficient of genotypic determination (H2) was 70.28 for NF and was considered high, indicating genetic variation in the genotypes tested. Estimates of genotypic correlation coefficients (rG), phenotypic (rf) and environmental (ra) had a lower magnitude values (<0.70). The fresh root weight data, dry root weight and root volume showed no significant effect. The analysis of the simple Pearson correlation was significant and positive between the variables dry weight (g) and root volume (cm3), with no relation to resistance of the cyst nematode (NF and FI), among the lines evaluated.